SOCIAL MOVEMENT DERIVED PUBLIC SPACES: A FOCUS ON GEZI PROTEST - Erdonmez, M. Ebru; Ataol-Akpinar, Ozlemnur (STEF92 TECHNOLOGY LTD, 2014)
Space does not occur only as a physical structure, also occurs with human activity, such as the occurrence of public spaces. They find meaning with human activities beside their definition by boundaries and design. The emergence of public spaces by human activity also helps to reach to a level of political human identity from the level of being human. In this study, spatial footprints of this mutual existence are read through social movements. Urban spaces are not considered only with their physical features but also meanings of social, sociological, psychological, as a whole. With different points of view, it is seen that public spaces devolve their situations and functions to private spaces in intensive ways. Changing relationship between the usage of public and private spaces is getting interests of researchers who studied on the evolution of the modern society. These researches have mainly two focus points. First indicates that there is a relationship between changing usage of public spaces intensively, and the appearance of living rooms instead of squares and streets as public spaces, which bring along to zoom in on personality problems by individuals. Second focus point examines conditions of people over their encouragement that occurs in order to explain their feelings to others. Recent social movements can give a perspective with an understanding to these conditions. The conditions that are comprised by social movements emphasize the importance of public spaces in cities and on social life, together with the right to the city, which on the other hand gave a rise to social movements. Therefore, it can be said that the lack of public space makes mutual relationship/communication between people and groups widely pointless. This study aims to analyze social structure - public space relationship and utilization of square as a public space. Perception of square within the society, its importance and essentiality in urban texture, its physical and symbolic features, its analysis as a sustainable living environment will be the main areas to be covered within this context. The study will be concluded by the analysis of the recent transformation of Istanbul Taksim Cumhuriyet Square and the reflection of Gezi Protest to this transformation.
Keywords: public space; social movements; human activity; social life; Istanbul; Arts & Humanities - Other Topics